Influencia del comportamiento reproductivo por acción del fotoperiodo en yeguas que habitan en la zona ecuatorial - Agualongo Manobanda, Ingrid Denisse (2022)
The females are seasonally polyestrous and the photoperiod programs the reproductive activity on the days with the greatest amount of light hours, this happens every year in the summer, the females present estrous cycles and therefore, they can conceive. In the ovulatory season, the mare shows estrous cycles; this occurs repeatedly, while the mare does not conceive and the appropriate photoperiod conditions remain, generally days with more daylight hours. To establish the interovulatory intervals, the hypothalamus-pituitary-gonadal axis is stimulated, with the additional contribution of the uterus. The effect that the photoperiod has on sexual activity is particularly mediated by melatonin, this is one of the hormones synthesized by the pineal gland. The synthesis and secretion of melatonin occurs only in periods of darkness, therefore, melatonin production increases in the autumn months and decreases in spring. As day length increases, the mare enters a transition phase in which the ovaries return to cyclic activity and produce eggs or follicles. During this transition, the follicles do not always ovulate due to low levels of LH. The qualitative and exploratory method will be used based on data from scientific journals, web pages, information obtained from academic Google bibliographies and scientific articles; knowing that this exploratory data collection technique is the most suitable for the analysis of the influence of reproductive behavior by the action of the photoperiod in mares that live in the equatorial zone.